2017
DOI: 10.1038/s41467-017-01460-0
|View full text |Cite|
|
Sign up to set email alerts
|

Mutational and putative neoantigen load predict clinical benefit of adoptive T cell therapy in melanoma

Abstract: Adoptive T-cell therapy (ACT) is a highly intensive immunotherapy regime that has yielded remarkable response rates and many durable responses in clinical trials in melanoma; however, 50–60% of the patients have no clinical benefit. Here, we searched for predictive biomarkers to ACT in melanoma. Whole exome- and transcriptome sequencing and neoantigen prediction were applied to pre-treatment samples from 27 patients recruited to a clinical phase I/II trial of ACT in stage IV melanoma. All patients had previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
311
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 357 publications
(329 citation statements)
references
References 60 publications
5
311
1
Order By: Relevance
“…Filtering algorithms and cutoffs for putative germline variants, variant allele frequency (VAF), and FFPE‐induced deamination artefacts vary between assays and can be affected by biological and preanalytical factors. For example, VAF cutoffs can vary from 0.5 to 10%, with lower thresholds increasing the risk of including false‐positives arising from contamination or sequencing artefacts …”
Section: Variation In Tmb Assessment and Factors That Impact Tmb Outputmentioning
confidence: 99%
See 1 more Smart Citation
“…Filtering algorithms and cutoffs for putative germline variants, variant allele frequency (VAF), and FFPE‐induced deamination artefacts vary between assays and can be affected by biological and preanalytical factors. For example, VAF cutoffs can vary from 0.5 to 10%, with lower thresholds increasing the risk of including false‐positives arising from contamination or sequencing artefacts …”
Section: Variation In Tmb Assessment and Factors That Impact Tmb Outputmentioning
confidence: 99%
“…For example, VAF cutoffs can vary from 0.5 to 10%, with lower thresholds increasing the risk of including false-positives arising from contamination or sequencing artefacts. 4,24,36,48,[72][73][74] For calculation of the TMB denominator, genome coverage and bioinformatic parameters must be considered. Most studies have reported a TMB value in mut/Mb, whereas others have reported total mutations per tumor (WES studies); this makes it difficult to compare TMB values across patients and studies.…”
Section: Variation In Tmb Assessment and Factors That Impact Tmb Oumentioning
confidence: 99%
“…Indeed, ACT with tumor infiltrating lymphocytes (TIL) harboring NeoAg specificities has induced tumor regression in patients with metastatic breast cancer and melanoma 31,32 . Furthermore, patients with higher mutational burden malignancies (and therefore a greater diversity of NeoAg targets) experience a greater response rate to both TIL ACT and ICB 33–35 . NeoAg‐specific T cells have also been identified as effectors of antitumor immunity in mouse models 36–38 .…”
Section: Which Antigens Do T Cells Recognize In Cancer?mentioning
confidence: 99%
“…31,32 Furthermore, patients with higher mutational burden malignancies (and therefore a greater diversity of NeoAg targets) experience a greater response rate to both TIL ACT and ICB. [33][34][35] NeoAg-specific T cells have also been identified as effectors of antitumor immunity in mouse models. [36][37][38] Specifically, NeoAg-specific T cell populations increased in frequency and a greater percentage produced effector cytokines in mice bearing MCA-induced sarcomas receiving ICB.…”
Section: Which Antigens Do T Cells Recognize In Cancer?mentioning
confidence: 99%
“…Balachandran et al 2017; Brown et al 2014; Gros et al 2016; Hodges et al 2017; Lauss et al 2017; Linnemann et al 2015; Luksza et al 2017; Matsushita et al 2012; McGranahan et al 2016; Ock et al 2017; Pritchard et al 2015a; Rizvi et al 2015; Robbins et al 2013; Snyder et al 2014; Tran et al 2016; Van Allen et al 2015; van Rooij et al 2013; Verdegaal et al 2016). While these various tools have an important role to play in the prediction of immunogenic antigens, the majority of the identified epitopes do not initiate an immune response (e.g.…”
Section: Identification Of Neoantigensmentioning
confidence: 99%